Design and evaluation of novel triazole derivatives as potential anti-gout inhibitors: a comprehensive molecular modeling study - Er-rajy, Mohammed; El fadili, Mohamed; Zarougui, Sara; Mujwar, Somdutt; Aloui, Mourad; Zerrouk, Mohammed; Hammouti, Belkheir; Rhazi, Larbi; Sabbahi, Rachid; Alanazi, Mohammed M.; Azzaoui, Khalil; Salghi, Rachid; et al. (Frontiers in Chemistry, 2025)
IntroductionGout is the most common inflammatory arthritis, characterized by hyperuricemia, tophus formation, joint disease, and kidney stones. Uric acid, the final byproduct of purine catabolism, is eliminated via the kidneys and digestive system. Xanthine oxidase (XO) catalyzes the conversion of hypoxanthine and xanthine into uric acid, making XO inhibitors crucial for treating hyperuricemia and gout. Currently, three XO inhibitors are clinically used, showing significant efficacy. A molecular modeling study on triazole derivatives aims to identify novel XO inhibitors using 3D-QSAR, molecular docking, MD simulations, ADMET analysis, and DFT calculations. These computational approaches facilitate drug discovery while reducing research costs.MethodsOur work focuses on a series of synthesized anti-xanthine oxidase inhibitors, aiming to develop new inhibitors. A computational study was carried out to identify the xanthine oxidase inhibitory structural features of a series of triazole inhibitors using computational method.ResultsA model based on CoMFA and CoMSIA/SEA has been built to predict new triazole derivatives.DiscussionThe optimal model established from CoMFA and CoMSIA/SEA was successfully evaluated for its predictive capability. Visualization of the contour maps of both models showed that modifying the substituents plays a key role in enhancing the biological activity of anti-gout inhibitors. Molecular docking results for complexes N°8-3NVY and N°22-3NVY showed scores of −7.22 kcal/mol and −8.36 kcal/mol, respectively, indicating substantial affinity for the enzyme. Complex N°8-3NVY forms two hydrogen bonds with SER 69 and ASN 71, three alkyl bonds with ALA 70, LEU 74, and ALA 75, and one Pi-Pi T-shaped bond with PHE 68. Complex N°22-3NVY forms three hydrogen bonds with HIS 99, ARG 29, and ILE 91, and one halogen bond with LEU 128 at 3.60 Å. A MD study revealed that the N°22-3NVY complex remained highly stable throughout the simulation. Therefore, we proposed six new molecules, their anti-gout inhibitory activities were predicted using two models, and they were evaluated for Lipinski's rule, and ADMET properties. The results show that both Pred 4 and Pred 5 have better pharmacokinetic properties than the height potent molecule in the studied series, making these two compounds valuable candidates for new anti-gout drugs. Subsequently, using DFT study to evaluate the chemical reactivity properties of these two proposed compounds, the energy gap results revealed that both molecules exhibit moderate chemical stability and reactivity.